Pengembangan Aplikasi Mobile Pemesanan Jasa Laundry Berbasis Android - Fajri Fernanda; Adam Hendra Brata; Eriq Muh. Adams Jonemaro (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Laundry service providers are businesses that are in great demand today. The laundry service process is divided into several stages, first stage is laundry registration stage, clothing processing, and clothing collection. Snapwash is a laundry service provider based in the city of Bekasi. Snapwash wants to provide a laundry service booking service directly to the front door of the user who can be ordered through the application then the agent will pick up the clothes to be laundry and deliver them to Snapwash or one of the partners working with Snapwash. Therefore, the Android-based Snapwash application is made to help customers, through the application the user can order laundry services, tracking progress, get push notification related to laundry that is being processed and can send laundry related questions and make laundry complaints via chatbots developed using Dialogflow. Snapwash is also made a website admin system to manage laundry orders from customers. In this study, this application was developed by applying the prototyping method because it can help in the process of extracting user needs. The implementation of this application program code uses the Kotlin programming language. Based on the results of unit testing and validation testing get 100% valid results which can be concluded that this application has met and in accordance with user needs. The results of usability testing using SUS (System Usability Scale) as an instrument get the result of 75.5 which can be concluded that the application is in the Acceptable category and according to user needs.